A medium composition containing normal resting glucose that supports differentiation of primary human airway cells - Morgan, Rachel; Manfredi, Candela; Easley, Kristen F.; Watkins, Lionel D.; Hunt, William R.; Goudy, Steven L.; Sorscher, Eric J.; Koval, Michael; Molina, Samuel A. (Scientific reports, 2022)
Primary cells isolated from the human respiratory tract are the state-of-the-art for in vitro airway epithelial cell research. Airway cell isolates require media that support expansion of cells in a basal state to maintain the capacity for differentiation as well as proper cellular function. By contrast, airway cell differentiation at an air–liquid interface (ALI) requires a distinct medium formulation that typically contains high levels of glucose. Here, we expanded and differentiated human basal cells isolated from the nasal and conducting airway to a mature mucociliary epithelial cell layer at ALI using a medium formulation containing normal resting glucose levels. Of note, bronchial epithelial cells expanded and differentiated in normal resting glucose medium showed insulin-stimulated glucose uptake which was inhibited by high glucose concentrations. Normal glucose containing ALI also enabled differentiation of nasal and tracheal cells that showed comparable electrophysiological profiles when assessed for cystic fibrosis transmembrane conductance regulator (CFTR) function and that remained responsive for up to 7 weeks in culture. These data demonstrate that normal glucose containing medium supports differentiation of primary nasal and lung epithelial cells at ALI, is well suited for metabolic studies, and avoids pitfalls associated with exposure to high glucose.